2007
DOI: 10.1590/s0037-86822007000400003
|View full text |Cite
|
Sign up to set email alerts
|

Domiciliation of Triatoma pseudomaculata (Corrêa e Espínola 1964) in the Jequitinhonha Valley, State of Minas Gerais

Abstract: Impact of the vector control program was evaluated eight years after implantation of epidemiological surveillance for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.…”
Section: Discussionsupporting
confidence: 53%
“…In the northeast of Brazil T. pseudomaculata has great importance for epidemiological surveillance of Chagas disease, its being the most frequent species after T. brasiliensis 15,42 . Some studies have suggested that the increasing presence of T. pseudomaculata in the domiciliary environment is related to climate change, deforestation, and cropland expansion 25,44 , which could explain the higher frequency of this species in the rural areas of Planaltina and Paranoá, observed in the present study.Regardless of the fact that it has remained the most collected species in cerrado areas of Brazil for the past years 18,45-47 , T. sordida presents a low risk of transmission of T. cruzi to humans because of its peridomiciliary behavior and marked ornithophily 15,34,[46][47] . Some studies show that zones of higher occurrence of T. sordida correspond to those of higher and older farm exploration 33 , which may justify the higher frequency of this species in Planaltina.…”
supporting
confidence: 53%
“…The species is most frequent in the peridomiciles, usually feeds on birds 27 and has lower rates of infestation, colonization, and infection 7 . However, Assis et al 28 suggest that the increasing presence of T. pseudomaculata in household environments is related to climate change, deforestation, and expansion of agricultural areas. Moreover, the known ability of dispersal by flight guided by artificial light of T. pseudomaculata and T. brasiliensis 29 favors the invasion of households in the northeastern region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, T. pseudomaculata has become adapted to artificial ecotopes, becoming easily captured in peridomiciles, mainly in henhouses (Assis et al 2007). In Jaguaruana, this triatomine has been found in peridomiciles as well as in intradomiciles, where it can establish colonies (Sarquis et al 2006), a fact that was also observed in Sobral, a municipality located in the state of Ceará (Frota et al 1999).…”
Section: Discussionmentioning
confidence: 99%